TEACHING ENGLISH METHOD: ROLE PLAY TO INCREASE SPEAKING ABILITY FOR NURSING STUDENT OF STIKES BINA SEHAT PPNI MOJOKERTO - Asef Wildan Munfadlila (Institut Pendidikan Tapanuli Selatan, 2022)
Role play is a technique which involves fantasy or imagination to be someone else or to be ourselves in a specific situation for a while, improving dialogue and creating a real world in scenario. The aim of this study is to find out whether there is positive significant influence of using role play in teaching descriptive text on the students’ speaking ability or not. The pre-experimental quantitative design was usedso the data can be evaluated by using statistical analysis. The population of the study was the 3rd grade student of STIKes Bina Sehat PPNI Mojokerto. And the sample class was III-C class, consist of 43 students. To compute the data, the writer used pre-test and post-test one group design. The sample class was given pre-test before they got the treatment and the post-test after they got the treatment. Then, the result of the pre-test and post-test was analyzed by using the test formula.The result of the study showed that there was significance influence of using role play in teaching narrative text on the students’ speaking ability. The result of statistical analysis shows that the value of t-result is 22 > t-table significant level 1% is 2.704. It means that the result of the study is significant in which Ha is accepted and Ho is rejected.From the analysis above, it can be concluded that there is a significant influence of using role play on the students’ speaking ability.